2021
DOI: 10.1111/ane.13529
|View full text |Cite
|
Sign up to set email alerts
|

Initial cognitive impairment predicts shorter survival of patients with glioblastoma

Abstract: Reperfusion therapies have markedly improved the outcomes after acute ischemic stroke (AIS). 1,2 The therapeutic window has expanded, but it remains narrow for most patients. [1][2][3][4] The sooner treatment is initiated after symptom onset, the better chance for a good outcome. 5,6 Prehospital delay, which includes both patient delay and system delay, is the main reason for low reperfusion therapy rates at the stroke centres. 7,8 Patient delay denotes the time from symptom onset until contact to a healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…In addition, the top ten GO terms enriched by downregulated DEGs all had a strong link with synapse formation, stabilization, and signal transduction ( Figure 5(g) ). Clinically, patients with high-grade glioma tend to develop degenerative diseases such as memory loss and cognitive impairment, and it has been demonstrated that impaired cognitive function is associated with shorter survival in glioblastoma patients [ 42 ]. Furthermore, pyroptosis is strongly associated with Alzheimer's disease progression, and GSDMD serves as an important marker for AD [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the top ten GO terms enriched by downregulated DEGs all had a strong link with synapse formation, stabilization, and signal transduction ( Figure 5(g) ). Clinically, patients with high-grade glioma tend to develop degenerative diseases such as memory loss and cognitive impairment, and it has been demonstrated that impaired cognitive function is associated with shorter survival in glioblastoma patients [ 42 ]. Furthermore, pyroptosis is strongly associated with Alzheimer's disease progression, and GSDMD serves as an important marker for AD [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…ns: not significant. * * p < 0:01, * * * p < 0:001, and * * * * p < 0:0001. explain to some extent the clinical phenomenon of cognitive dysfunction associated with poor prognosis in glioblastoma patients [42]. Notably, the Riskscore was significantly positively correlated with BMDM infiltration, while the singlecell transcriptomics further demonstrated that NLRC4+ CASP1+ GSDMD+ and CASP4+ GSDMD+ cells were concentrated in a specific peripheral-derived BMDM cluster.…”
mentioning
confidence: 90%
“…Only some patients were referred to mental health services, with some only available through external providers, presenting an access barrier. Australian clinical practice guidelines and OCPs indicate early consistent psychosocial care of brain cancer patients and their carers is critical [ 10 , 18 , 24 , 25 ]. Most cognitive rehabilitation intervention programs reported improvements in patients' cognitive test-performance [ 26 ] and could be considered for inclusion in psychosocial care of HGG patients.…”
Section: Discussionmentioning
confidence: 99%
“…We identified low referrals to speech therapists, despite the frequent occurrence of speech aberrations (eg. expressive and receptive dysphasia) [ 18 ] and increasing communication deficits over time [ 28 ]. Occasionally issues relating to swallowing emerge, which can be addressed by speech pathologists [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to emerging as possible side effects of ferroptosis pathway manipulation, cognitive impairment was also described as a glioblastoma symptom ( 75 ). Cognitive impairment often delays diagnosis and is associated with a reduced overall survival ( 75 ), which should be considered when assessing cognitive dysfunction as potential side effects of add–on drugs.…”
Section: Ferroptosis In Healthy Neurons and Potential Side–effects Of Ferroptosis Inductionmentioning
confidence: 99%